Combining ability of tomato inbred lines to bacterial wilt resistance - Lopes,Gabriel Lourenço (2022)
ABSTRACT Tomato is one of the most important crops worldwide. Bacterial wilt (BW), caused by Ralstonia spp., is a major disease for tomato production around the world, especially in tropical and subtropical regions. Currently in Brazil, only commercial hybrids are available as resistant rootstocks for use in infested areas, and we lack information regarding resistance to aggressive strains. Thus, the aims of this work were to estimate combining abilities of five tomato inbred lines and hybrids and to identify resistant genotypes for using as rootstocks resistant to Ralstonia solanacearum biovar 2, phylotype II, one of the most aggressive strains in Brazil. Combining abilities for BW resistance were assessed through full diallel crossings among five tomato inbred lines without reciprocals. The experiment was carried out in a greenhouse, in a complete randomized blocks design, using 15 genotypes (hybrids and parents). Additive genetic effects showed to be the most important for controlling bacterial wilt. The inbred line Hawaii 7996 exhibited the highest general combining ability among the five parents assessed. The hybrid Hawaii 7996 × Rodade was the best crossing in terms of resistance and specific combining ability, which was greater than those of all other hybrids. Although Hawaii 7996 remains as a major source for BW resistance, further researches are needed to better understand the resistance dynamics, seeking to develop hybrids with transgressive segregations and more stable resistance against aggressive strains and thrive under environmental conditions highly favorable to bacterial wilt infection.